2021
DOI: 10.1109/access.2021.3117567
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Beetle Antennae Search Algorithm Based on the Elite Selection Mechanism and the Neighbor Mobility Strategy for Global Optimization Problems

Abstract: Aiming at the shortcoming that the basic beetle antennae search algorithm fails to consider the differences between individuals and dynamic information in the searching process, this paper proposed a new search algorithm based on the elite selection mechanism and the neighbor mobility strategy. The elitist selection mechanism is used to weaken beetles having bad performance and generate new beetles to ensure diversity and adaptability in the whole population. The neighbor mobility strategy will guide the algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Then, the position is updated based on the evaluation of the objective function. eBAS was compared with nine other metaheuristic algorithms, including BA, Biogeography-Based Optimization (BBO) (Qian et al 2022), ABC, PSO, Cuckoo Search (CS) (Shao and Fan 2021), Harmony Search (HS) (Wu et al 2020), (Mirjalili et al 2014), Teaching-Learning-Based Optimization (TLBO) (Neshat et al 2014), and FA. eBAS demonstrated exceptional performance in multiple optimization examples with continuous and/or discrete variables, especially in solving practical-sized problems with numerous design variables and complex constraints.…”
Section: Parameter Adjustment Improved Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the position is updated based on the evaluation of the objective function. eBAS was compared with nine other metaheuristic algorithms, including BA, Biogeography-Based Optimization (BBO) (Qian et al 2022), ABC, PSO, Cuckoo Search (CS) (Shao and Fan 2021), Harmony Search (HS) (Wu et al 2020), (Mirjalili et al 2014), Teaching-Learning-Based Optimization (TLBO) (Neshat et al 2014), and FA. eBAS demonstrated exceptional performance in multiple optimization examples with continuous and/or discrete variables, especially in solving practical-sized problems with numerous design variables and complex constraints.…”
Section: Parameter Adjustment Improved Algorithmmentioning
confidence: 99%
“…Rigorous evaluations through standard function tests revealed that BAS-ABC achieves a more rapid convergence and superior accuracy in comparison to the conventional ABC and PSO, albeit with a sensitivity to parameter configurations. Furthering this domain, Zhang et al introduced an iteration of the BAS-ABC algorithm (Shao and Fan 2021),, which, upon deriving optimal adaptive values and positions via BAS, employs these positions as food source coordinates within the ABC framework. The algorithm executes BAS iterations commensurate with the number of food sources identified in ABC.…”
Section: Artificial Bee Colony Algorithmmentioning
confidence: 99%